Latin America and the Caribbean : looking ahead after the millennium development goals : regional monitoring report on the Millennium Development Goals in Latin America and the Caribbean, 2015 - Gerstenfeld, Pascual (UN ECLAC SantiagoCL, 2015)
Affords a concise descriptive view of the progress achieved by Latin America and the Caribbean in respect of the Millennium Development Goals. Makes extensive use of infographics, including tables, figures and descriptive statistics, alongside brief explanatory texts on focus on core aspects of the region's progress towards achievement of the goals. Includes references to developments in other world regions, and points to the heterogeneity of national trends in Latin America and Caribbean, on the basis of a selection of relevant indicators that illustrate the countries' performance on individual goals and their respective targets.